The Working Capital Concept. - Fess, Philip E. (The Accounting Review, 1966)
Abstract The core of the working capital concept has been subjected to considerable change over the years. A few decades ago the concept was viewed as a measure of the debtor's ability to meet his obligations in case of liquidation. The prime concern was with whether or not the current assets were immediately realizable and available to pay debts in case of liquidation. In applying this measure a one-year period was frequently used to classify assets and liabilities as current. That is, current assets were those realizable and current liabilities were those due within one year. The focus of attention in recent years has shifted from this liquidation point of view towards the "operating cycle" point of view. This view emphasizes the ability of the firm to pay its maturing obligations from the funds generated by current operations. The article discusses question related to analysis of working capital and the presentation of the amount of working capital at a particular point in time to indicate a rough measure of the "margin or buffer" presently available to meet currently maturing obligations and the presentation of the flow of working capital for past periods and the expected flow covering future periods.